Increasing the take-up of public health services: An experiment on nudges and digital tools in Uruguay - Ana Cuesta; Lucia Delgado; Sebastián Gallegos; Benjamin Roseth; Mario A. Sánchez (Inter-American Development Bank (IDB), 2021)
In this paper, we test whether promoting digital government tools increases the take-up of an important public health prevention service: cervical cancer screening. We implemented an at-scale field experiment in Uruguay, randomly encouraging women to make medical appointments with a digital application or reminding them to do it as usual at their local clinic. Using administrative records, we found that the digital application nearly doubled attendance of a screening appointment compared to reminders and tripled the rate compared to a pure control group (3.2 percentage point increase over a base of 1.9 percent). Survey data suggests that the impacts of the intervention were mostly mediated by reduced transaction costs. Our results highlight the potential of investing in digital government to improve the take-up of public services.
Keywords: I12; I15; I18; D90; D91; 330; information; transaction costs; public services; text messages; digital government; health outcomes; cancer screening; women; behavioral economics; field experiment